An Assessment of Cough Medicine Dispensing Practice to Children Under Two Years Old in Pharmacies in Ho Chi Minh City Using Simulated-Patient Method - Quyen Thi Ngoc Phan; Van Thi Truong; Thanh Ngoc Pham; Ho Nhu Nguyen; Quynh Thi Huong Bui (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2020)
Over-the-counter (OTC) cough and cold medications (CCMs) have been used to treat the symptoms of upper respiratory infection in children for decades. The safety of CCMs in children has been questioned. The data on knowledge of pharmacists in supplying cough medicines for children under two years have been limited. This study aimed to evaluate the pharmacists’ dispensing decisions to manage the cough in children under two years old. A descriptive cross-sectional was carried out in 300 pharmacies in 15 districts in Ho Chi Minh City, Vietnam. The pharmacists were interviewed by a simulated patient. The results showed that, information that pharmacists actively asked the client about the patient and disease symptoms was limited. Most pharmacists did not provide adequate instructions and counsel about using drugs for clients. Only 22/300 (7.33%) of pharmacists appropriately provided cough medicines for children under 2 years old. The main reason of inappropriateness was the deficiency of knowledge about updated contraindication of N-acetylcysteine (93.17%). Pharmacists in pharmacies located in districts 3, 11 and Binh Thanh had higher rate of rational provision than those in other districts. A good and full understanding of the patient symptom helped the pharmacists supply cough medicines more reasonably. The limited caution of pharmacists and the low proportion of pharmacists updating contraindication of N-acetylcysteine should be considered as a warning sign in pharmacy practice in Ho Chi Minh City, Vietnam.